Population, providence and empire The churches and emigration from nineteenth-century Ireland - Roddy, Sarah (Manchester University Press, 2019)
The book knits together two of the most significant themes in the social and cultural history of modern Ireland - mass emigration and religious change - and aims to provide fresh insight into both. It addresses the churches' responses to emigration, both in theory and in practice. The book also assesses how emigration impacted on the churches both in relation to their status in Ireland, and in terms of their ability to spread their influence abroad. It first deals with the theoretical positions of the clergy of each denomination in relation to emigration and how they changed over the course of the nineteenth century, as the character of emigration itself altered. It then explores the extent of practical clerical involvement in the temporal aspects of emigration. This includes attempts to prevent or limit it, a variety of facilitation services informally offered by parish clergymen, church-backed moves to safeguard emigrant welfare, clerical advice-giving and clerically planned schemes of migration. Irish monks between the fifth and eighth centuries had spread Christianity all over Europe, and should act as an inspiration to the modern cleric. Tied in with this reading of the past, of course, was a very particular view of the present: the perception that emigration represented the enactment of a providential mission to spread the faith.